2005
DOI: 10.1597/03-107.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Protocol for Maxillary Protraction in Cleft Patients: Repetitive Weekly Protocol of Alternate Rapid Maxillary Expansions and Constrictions

Abstract: Maxillary protraction using the 2-hinged expander, a repetitive weekly protocol of Alternate Rapid Maxillary Expansions and Constrictions, and intraoral protraction springs is most effective, with stable results at 2-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
180
4
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(199 citation statements)
references
References 10 publications
0
180
4
15
Order By: Relevance
“…Liou 18 introduced a method called alternate rapid maxillary expansion (Alt-RAMEC) protocol to increase the skeletal effects of maxillary protraction, and several clinicians [19][20][21] reported the increased skeletal effects of this method when performed prior to maxillary protraction. To our knowledge, none of the previous studies evaluated the effects of maxillary protraction with Alt-RAMEC protocol on pharyngeal airway dimensions and hyoid bone position.…”
Section: Introductionmentioning
confidence: 99%
“…Liou 18 introduced a method called alternate rapid maxillary expansion (Alt-RAMEC) protocol to increase the skeletal effects of maxillary protraction, and several clinicians [19][20][21] reported the increased skeletal effects of this method when performed prior to maxillary protraction. To our knowledge, none of the previous studies evaluated the effects of maxillary protraction with Alt-RAMEC protocol on pharyngeal airway dimensions and hyoid bone position.…”
Section: Introductionmentioning
confidence: 99%
“…The longterm treatment prognosis of Angle's Class III malocclusions tends to be better if the malocclusion is caused by maxillary deficiency rather than by mandibular prognathism. 28 New treatment protocols are emerging for maxillary traction and research should be conducted alternating rapid expansion and constriction of the maxilla, where previous studies 14,15 reported an average protraction of 5.8 mm at point A. It was conducted a study 24 using anchorage implants in the search for a device capable of providing an extremely stable and secure anchorage in maxillary orthopedic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…: Il n'y a aucune preuve convaincante que l'expansion palatine associée à la protraction maxillaire facilite le mouvement de la partie médiane de la face vers l'avant. Eric Jein-Wein Liou [38,83], de Taiwan, encourage l'ouverture et la fermeture de la suture palatine médiane 4 à 6 fois, pour desserrer les sutures médio-faciales. Pour moi, cette procédure semble assez drastique étant donné que l'action proposée affecte l'ensemble des os crâniens.…”
Section: Biomécanique Efficace Et Individualisée Paunclassified